Oral Vitamin B12 Replacement for the Treatment of Pernicious Anemia - Chan, Catherine Qiu Hua; Low, Lian Leng; Lee, Kheng Hock (Frontiers in Medicine, 2016)
Many patients with pernicious anaemia are treated with lifelong intramuscular vitamin B12 replacement. As early as the 1950s, there were studies suggesting that oral vitamin B12 replacement may provide adequate absorption. Nevertheless, oral vitamin B12 replacement in patients with pernicious anaemia remains uncommon in clinical practice. The objective of this review is to provide an update on the effectiveness of oral vitamin B12 for the treatment of pernicious anaemia, the recommended dosage and the required frequency of laboratory test and clinical monitoring. Relevant articles were identified by PubMed search from 1 January 1980 to 31 March 2016 and through hand search of relevant reference articles. Two randomised controlled trials, three prospective papers, one systematic review and three clinical reviews fulfilled our inclusion criteria. We found that oral vitamin B12 replacement at 1000mcg daily was adequate to replace vitamin B12 levels in patients with pernicious anaemia. We conclude that oral vitamin B12 is an effective alternative to vitamin B12 intramuscular injections. Patients should be offered this alternative after an informed discussion on the advantages and disadvantages of both treatment options.